A 'real‐world' retrospective multi‐centre cohort study comparing infliximab and adalimumab for the maintenance of remission in ulcerative colitis. Issue 4 (19th June 2021) - Kronsten, Victoria Tatiana; Colwill, Michael J.; Nayeemuddin, Shadab; Limdi, Jimmy K.; Selinger, Christian; Scott, Glyn; Al‐Hillawi, Lulia; Salehi, Shayon; Blaker, Paul; Chung‐Faye, Guy; Kent, Alexandra J.; Dubois, Patrick; et al.
Abstract: Background: Anti‐tumour necrosis factor therapy is an established treatment for moderate‐to‐severely active ulcerative colitis (UC). Recent network meta‐analyses of controlled trial data have indicated a superiority of intravenous drugs (infliximab) over subcutaneous (adalimumab). We conducted a retrospective multi‐centre cohort study to determine the comparative effectiveness of these two drugs. Methods: Patients with UC administered infliximab or adalimumab as their first biologic, identified from the therapy databases of five UK hospitals, were included, if they had completed induction and were on maintenance treatment. Patients receiving infliximab as 'rescue' therapy for acute severe UC were excluded. The primary end‐points for comparison were the number of patients remaining on initial therapy (infliximab or adalimumab) at 52 weeks and the number of patients in clinical remission at 52 weeks (Simple Clinical Colitis Activity [SCCAI] score ≤ 3). Results: Seventy‐eight infliximab and 63 adalimumab patients were analysed. At 52 weeks, 83% of infliximab patients and 59% of adalimumab patients remained on therapy ( P  = 0.001). At 52 weeks, 62% of the infliximab group were in clinical remission compared to 32% of the adalimumab group ( P  = 0.0004). Primary non‐response was reported in 24% of adalimumab patients and 5% of infliximab patients ( P  = 0.001). There were no significant differences in colectomy rates or hospital admission for acute flares at 52 weeks. Conclusions: Our real‐world results affirm the findings of network meta‐analyses of clinical trials, suggesting that infliximab is superior to adalimumab in the maintenance of remission in UC up to 52 weeks.